Settlement at the Margins: Discussion - Dyer, Christopher (Medieval Settlement Research, 2025)
This discussion of the issues raised by contributions to the seminar endorses their focus on the margins themselves, rather than seeing them as inferior appendages. It raises questions about the economy of the settlements, and their fluctuating fortunes.